Activity of Povidone in Recent Biomedical Applications with Emphasis on Micro- and Nano Drug Delivery Systems - Ewelina Waleka; Zbigniew Stojek; Marcin Karbarz (MDPI AG, 2021)
Due to the unwanted toxic properties of some drugs, new efficient methods of protection of the organisms against that toxicity are required. New materials are synthesized to effectively disseminate the active substance without affecting the healthy cells. Thus far, a number of polymers have been applied to build novel drug delivery systems. One of interesting polymers for this purpose is povidone, pVP. Contrary to other polymeric materials, the synthesis of povidone nanoparticles can take place under various condition, due to good solubility of this polymer in several organic and inorganic solvents. Moreover, povidone is known as nontoxic, non-carcinogenic, and temperature-insensitive substance. Its flexible design and the presence of various functional groups allow connection with the hydrophobic and hydrophilic drugs. It is worth noting, that pVP is regarded as an ecofriendly substance. Despite wide application of pVP in medicine, it was not often selected for the production of drug carriers. This review article is focused on recent reports on the role povidone can play in micro- and nano drug delivery systems. Advantages and possible threats resulting from the use of povidone are indicated. Moreover, popular biomedical aspects are discussed.